Associação entre a avaliação objetiva funcional e alterações nos testes sensoriais quantitativos em pacientes com osteoartrite de joelho. Um estudo transversal - Sette, Filipe Estevão (Universidade Federal de São Carlos, 2024)
Chronic painful diseases present considerable complexity, both for their resolution and understanding. Resulting in episodes of disability, these conditions can impact various aspects of the affected individuals' lives. Knee osteoarthritis (KOA) is a chronic, degenerative disease affecting millions worldwide. Furthermore, its growth rate in recent years has become a concern within the context of disabilities and high healthcare costs. Sensory alterations and changes in pain processing are frequently observed in individuals with osteoarthritis (OA). However, there is no consensus on the relationship between such alterations, functional performance, and objective physical activity in people with KOA. Given that sensory findings may predict functional characteristics in KOA individuals, the objective of this study was to investigate whether pain sensitivity is associated with functional performance and objective physical activity in patients with KOA. Methods: This study was designed as an observational model with cross-sectional analysis of collected data. Additionally, the study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. Anthropometric data were collected, and the McMaster Universities Osteoarthritis Index (WOMAC) questionnaire was administered. Subsequently, physical function tests were conducted, including chair sit-to-stand, 40-meter fast-paced walking, and stair climb-and-descent tests. Following these tests, an accelerometer was attached to the middle third of the right thigh and worn continuously for 7 consecutive days to obtain objective physical activity data. After accelerometer removal, quantitative sensory tests (QST) were performed, including pressure pain threshold (PPT), temporal summation (TS), and conditioned pain modulation (CPM), at two points: proximal (medial joint line of the most symptomatic knee) and a remote point (contralateral long flexor carpi muscle). Descriptive analysis of the variables was conducted, and normality and variance homogeneity were assessed. Hierarchical multiple linear regression analysis was used to determine the association between study variables. A significance level of 5% (p<0.05) was adopted for all analyses. Results: Only one association was found between variables: remote point CPM and the 40-meter fast-paced walking test. Moreover, no other associative measures were found in the study. Conclusion: Based on our results, central pain may impair gait speed in people with KOA, while objective physical activity, as evaluated by accelerometer, seems to reflect similar outcomes to functional performance when related to pain sensitization.
Association between objective functional assessment and changes in quantitative sensory testing in patients with knee osteoarthritis. A cross-sectional study
Keywords: Osteoartrite de joelho; Dor; Função; Atividade física objetiva; TSQ; Knee osteoarthritis; Pain; Function; Objective physical activity; QST; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL